IDENTIFICATION OF HIGH SCHOOL STUDENTS' COMPUTATIONAL THINKING SKILLS IN SOLVING BINOMIAL PROBABILITY PROBLEMS - Nur Agustiani (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This study aims to identify the computational thinking skills of high school students in solving binomial probability problems. This research uses a case study method with a descriptive qualitative approach. The subjects of this study were three students of class XI, where each student represented each category of mathematical ability in general, namely: low, medium, and high. Data collection using test and interview methods. Based on the results of data analysis using computational thinking stages, that found: 1) Students with high mathematical abilities can fulfill the stages of computational thinking skills in each given problem. 2) Students with medium mathematical abilities can’t always fulfill the stages of computational thinking. When unable to solve problems, students with medium mathematical abilities have problem formulation and abstraction skills. 3) Students with low mathematical abilities are not as good as students with medium or high mathematical abilities. Students with low mathematical ability cannot fulfill all stages of computational thinking when they cannot solve problems.